Multi-objective Optimization Model of Track Utilization for Depot-returning Urban Rail Transit Trains with Shunting Operation Constraints - ZHANG Zengchao; XU Peng; XIN Liping; FAN Rui; LI Chen; WU Zelin (Chengshi guidao jiaotong yanjiu)
［Objective］ To improve the impact of shunting operations on the track utilization for the depot-returning urban rail transit trains and enhance the train maintenance efficiency, it is necessary to optimize the track utilization of the depot-returning train with shunting operation constraints. ［Method］ Regarded as a depot-returning train, the transition train is incorporated into the early and late depot-returning plans respectively according to the shunting time. With the minimum number of shunting operations and the shortest running distance for maintenance as the objective function, and taking the constraints of shunting operations into account, a multi-objective optimization model for train track utilization is developed based on an improved grey wolf algorithm, featuring first for individual independent depot-returning plan (early and late depot-returning) and then for all depot-returning plans as a whole. In a case study of the track utilization plan for the depot-returning train on a metro line in Tianjin, the effectiveness and feasibility of the established optimization model are verified. ［Result & Conclusion］ The train running distance of the track utilization plan obtained from the proposed model is reduced by 65.7% compared with the manual plan (with a 25% reduction in the early depot-returning stage and a 77.7% reduction in the late depot-returning stage), and the number of train shunting operations is zero. The model can achieve the optimal arrangement of track utilization for the depot-returning train on the basis of satisfying the constraints of shunting operations such as train washing, maintenance, and departure on the next day.